Hybrid Electric Propulsion Design and Analysis Based on Regional Aircraft Mission - Wenjuan Shan; Shengze Bao; Shixuan Lin; Le Kang (World Electric Vehicle Journal)
Hybrid propulsion systems have become a focal point of low-carbon aviation research due to their advantages in energy savings, emissions reduction, and noise abatement. This study develops an integrated design methodology for hybrid propulsion systems for aircraft, incorporating multidisciplinary algorithms to establish an overall performance model. Building on this model, a comprehensive aircraft design platform was constructed, and its simulation capabilities were validated. Focusing on the mission requirements of a 180-seat narrow-body airliner, this study analyzed and compared the characteristics of three hybrid propulsion architectures, optimized their design schemes, and evaluated the key technologies for each architecture. A sensitivity analysis was conducted for critical technologies within the turboelectric architecture. The results indicate that, based on current data and future projections, a turboelectric system featuring batteries with a specific energy of 500 Wh/kg and installed motor power of 3 MW demonstrates superior performance, reduced fuel consumption, and no additional energy storage burden, making it the preferred propulsion solution. Furthermore, enhancing the utilization of aft-mounted fans and increasing the power blending coefficient can improve system performance. However, the maximum power blending coefficient is constrained to 27.25% by the specific motor power capacity.